Peredaran Kosmetik Pemutih Ilegal di Indonesia dan Upaya Penanggulangannya - Iin Febrianti Sende; Adin Wira Pramudita; M. Gafur Salafuddin; Edi Priyo Yunianto (Badan Pengawas Obat dan Makanan, 2020)
Whitening cosmetics are still popular in Indonesia, along with the stigma that white skin is idealized skin color. Woman with white skin acknowledges as beautiful woman. The increasing public demand for whitening cosmetics is exploited by crime offenders who produce and distribute illegal whitening cosmetics. The study was conducted by collecting inspection data and law enforcement data carried out by the Indonesian FDA and other criminal justice systems, direct research in the field, and online mapping through cyber patrol and Google Trends analysis to capture the distribution model of illegal whitening cosmetics in Indonesia, both those distributed offline as well as distributed online. The result of the study shows that illegal whitening cosmetics are produced then distributed offline and online in all provinces in Indonesia with various types of modus operandi, in line also with the high interest of searching for whitening cosmetics in online media. Illegal whitening cosmetics are known to have no marketing authorization and also contain prohibited ingredients, such as mercury, hydroquinone, tretinoin, and steroid. Many factors influence the supply chain stages of this illegal whitening cosmetics from upstream/supply (producers and distributors) to downstream/demand (consumers). Indonesian FDA must take the strategic step to minimize or reduce each of these factors, with repressive actions towards manufacturers and distributors, and preventive actions against consumers of illegal whitening cosmetics or through system/policy intervention.